Knowledge, Attitude, and Practice of Health Workers in a Tertiary Hospital in Ile-Ife, Nigeria, towards Ebola Viral Disease - Samuel Anu Olowookere; Emmanuel Akintunde Abioye-Kuteyi; Olusegun Kayode Adepoju; Oluwaseun Taiwo Esan; Temitope Michael Adeolu; Tolulope Kola Adeoye; Adesola Adebayo Adepoju; Adedayo Titilayo Aderogba (Journal of Tropical Medicine)
Background. Health workers are more prone to Ebola viral disease (EVD) than the general population. This study assessed the preparedness of health workers in the control and management of EVD. Methods. A descriptive cross-sectional study. Consenting 400 health workers completed a semistructured questionnaire that assessed participants’ general knowledge, emergency preparedness, and control and management of EVD. Data were analysed using descriptive and inferential statistics. Results. The mean age (SD) was 34.5 ± 8.62 years ranging from 20 to 59 years. Most participants were medical doctors (24.6%) and nurses (52.2%). The majority had practised <10 years (73.8%) and were aware of the EVD outbreak in the West African subregion (85.5%). Colleagues (40%) and radio (37.2%) were their major sources of information. Only 42% had good knowledge while 27% knew that there was no vaccine presently to prevent EVD. About one-quarter (24.2%) had low risk perception. The majority (89%) felt the hospital infection control policy was inadequate to protect against EVD. The only predictor of good knowledge was participants’ occupation. Conclusion. There is knowledge gap and poor infection control preparedness among respondents. Thus, knowledge and practices of health workers towards EVD need improvement.